Asymptomatic bacteriuria among antenatal women attending a tertiary care hospital in Kanchipuram: evaluation of screening tests and antibiotic susceptibility pattern - Jayachandran, Abirami Lakshmy; Gnanasambandam, Ukkiravel; Sangeetha, Balan K., A.V.; Vijayalakshmi, T. S. (International Journal of Research in Medical Sciences, 2016)
Background: Asymptomatic bacteriuria (ASB) occurring in pregnant women can lead onto complications like acute pyelonephritis, hypertensive disease of pregnancy, premature delivery and intrauterine growth retardation if untreated. Methods: The present study aims to estimate the occurrence of asymptomatic bacteriuria in antenatal women and to study the antibiotic susceptibility pattern of the isolates. The Gram staining, pus cell count and culture was performed for 120 urine samples. Antibiotic susceptibility testing was done by Kirby Baeur disk diffusion method. MRSA (Methicillin resistant Staphylococcus aureus) and ESBL (Extended spectrum Beta Lactamases) producers were identified by Standard guidelines. The sensitivity, specificity, negative predictive values and positive predictive values of Gram staining and pus cell count was calculated. Results: Out of the 120 samples 14 (11.66%) were positive for asymptomatic bacteriuria. The Gram staining showed specificity and negative predictive value of 95.2% and 98.1% respectively. Pus cell count showed a specificity and negative predictive value of 96.29% and 98.11% respectively. Escherichia coli were the predominant species isolated 5 (35.7%). Among the gram negative bacteria, amikacin and nitrofurantoin showed a susceptibility of 90% and 80% each. All the staphylococcus aureus isolates showed 100% sensitivity for nitrofurantoin. Two Klebsiella spp and one Escherichia coli isolate were identified as ESBL producers. Among the S. aureus isolates 3 were identified as Methicillin resistant (MRSA). Conclusions: Urine culture should be performed for all pregnant women irrespective of the symptoms and should be treated promptly to prevent the complications arising out of ASB.